Pengaruh Ukuran Perusahaan, Profitabilitas, Leverage dan Opini Audit Terhadap Audit Delay - Ameliana Salsabila; Kartika Hendra Titisari; Riana Rachmawati Dewi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Audit delay is the time interval between the closing date of financial books and the date of reporting by independent auditors. Delays in completing the audit of financial statements can hinder decision-making processes for stakeholders. This research investigates and analyzes the influence of company size, profitability, leverage, and audit opinion on audit delay. Purposive sampling was employed, gathering 96 samples from 16 companies in the food and beverage sector listed on the Indonesia Stock Exchange during the period from 2018 to 2023. Secondary data from financial reports were analyzed using multiple linear regression. The findings indicate that leverage has an impact on audit delay. However, company size, profitability, and audit opinion do not influence audit delay.